Precedence in the court of de Catholic Monarchs: Royal precedence as a communication tool in the royal entries of the Catholic Monarchs - González Díaz, Lara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The present study shows a review of the use of precedence in the royal entrances of the Catholic Monarchs. The objective is based on demonstrating that the court used this tool of the protocol according to the circumstances and the own interests of each moment, both from a symbolic point of view and from the point of view of royal communication. Precedence is used in these acts to divulge the identity of power, questioned since the beginning of the reign itself, the use of this in a particular way in some of the royal entries supports at all times the emblems defended by said court.